2018
DOI: 10.1093/neuros/nyy263
|View full text |Cite
|
Sign up to set email alerts
|

The Preventable Shunt Revision Rate: A Multicenter Evaluation

Abstract: PSRR is variable across institutions, but can be 50% or higher. While the PSRR may never reach zero, this study demonstrates that overall about a third of early failures are potentially preventable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Notably, only 4 of these 17 patients had hydrocephalus before craniotomy, while the remaining 13 patients presented without hydrocephalus before craniotomy for brain tumor (Table 2). In the literature, shunt-failure rates range from 16.9 to 28.8% at 3 months [4,7,36] and 9.17-77.3% at 6 months [7,8,[23][24][25]36] with median shunt-survival times from 22.5 days up to 5.2 years [23,25,35]. However, most of these studies have not been conducted of brain tumor patients as a separate cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, only 4 of these 17 patients had hydrocephalus before craniotomy, while the remaining 13 patients presented without hydrocephalus before craniotomy for brain tumor (Table 2). In the literature, shunt-failure rates range from 16.9 to 28.8% at 3 months [4,7,36] and 9.17-77.3% at 6 months [7,8,[23][24][25]36] with median shunt-survival times from 22.5 days up to 5.2 years [23,25,35]. However, most of these studies have not been conducted of brain tumor patients as a separate cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Although the main objective of treating hydrocephalus with VP shunts is to establish a permanent CSF diversion, achieving maximum VP shunt survival, defined as time from implantation to its malfunction, still remains challenging. Numerous studies have been published on postoperative shunting and shunt-survival rates with respect to the pediatric population [16], hemorrhage-related hydrocephalus [28,34], infections [4,8,24,25], shunting related to specific tumor types [3,19], and vascular brain malformations [15]. However, studies on shunt-survival rates and risks leading to shunt failure with respect to brain tumors remain scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Shunt insertion for CSF diversion becomes one of the procedures most prone to failure. Some studies showed the incidence of shunt failure of around 30–51% in the 1 st year after the shunt insertion[ 2 , 3 , 7 , 10 , 13 ] This number is almost 2-fold higher than the incidence of shunt revision during the first 12 months follow-up after the shunt procedure in our center which was 18.3%. There are several factors that might be involved in this difference including the nonexistence of a shunt registry in Indonesia compared to the developed countries where the shunt registry is available to accommodate the sustainable follow-up for patients who had a shunt procedure.…”
Section: Discussionmentioning
confidence: 79%
“…[ 13 , 16 ] The increasing age showed significant association as protective factor in both univariate and multivariate analyses as each additional year was associated with 20% of decreasing the risk of shunt failure leading to shunt revision. [ 3 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation